Anatomy and Topography of Coronary Sinus and Mitral Valve Annulus in Functional Mitral Regurgitation - Rottländer, Dennis; Saal, Martin; Ögütcü, Alev; Degen, Hubertus; Haude, Michael (Frontiers in Cardiovascular Medicine, 2022)
Background: We aimed to investigate the anatomical relationship of the coronary sinus (CS) and the mitral valve annulus (MVA) in patients with or without functional mitral regurgitation (FMR) using a multislice computed tomography (MSCT) software to determine (a) distance and angle of both CS and MVA plane and (b) mitral annulus geometry. Methods: A total of 215 patients with MSCT and CS to MVA topography evaluation were enrolled in this retrospective study. Results: This patient cohort included 145 patients without FMR (67.4%, FMR≤1+) and 70 patients (32.6%) with clinically relevant FMR (FMR≥2+). Distance and angulation of CS to MVA planes were highly variable. In all groups no significant correlation was documented between the distance or angle of CS to MVA planes and left ventricular ejection fraction, left ventricular end-diastolic diameter or left atrial volume. A significant increase in total CS length could be found in patients with FMR≥2+ compared to the FMR≤1+ group. MVA diameter, area and perimeter were significantly increased in FMR≥2+ compared to FMR≤1+. In the FMR≥2+ cohort 61% showed a distance of CS to MVA plane < 7.8mm and 58% revealed an angle of CS to MVA plane < 14.2°. Conclusion: Distance and angulation of CS to MVA topography using a MSCT approach are similar between patients with or without FMR, while CS length, MVA area, MVA perimeter, anterior-posterior diameter and intercommissural diameter are significantly increased in all FMR subgroups. However, approximately 60% of FMR≥2+ patients show favourable CS to MVA topography for indirect mitral annuloplasty.